"Hope Is Greater than Barriers": Creating a Pathway of Hope for Low-Income Families in Moving Out of Poverty. Issue 5 (29th July 2021) - Hong, Philip Young P.; Hong, Rana; Lewis, Dara; Swanson, Maribeth V.; Smith, Michael A.
ABSTRACT: This study explored a strength-based, anti-poverty program called Pathway of Hope (POH) of the Salvation Army based on the data that was collected from 11 focus groups consisting of 30 service users and 32 service providers in 2017. The results of the qualitative content analysis found four main categories for creating a pathway of hope: (a) case manager as a personal coach and spiritual accompanist; (b) goal attainment in the POH process; (c) relationship between hope and barriers; and (d) regional coordinator's modeling role for case managers. Implications for service delivery in social work practice and future research suggestions are discussed.